2007
DOI: 10.1111/j.1365-3059.2007.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

Branch cankers on citrus trees in Spain caused by Phytophthora citrophthora

Abstract: Considerable losses of citrus trees have been observed in the major citrus-growing areas of Spain. Samples were collected from 132 orchards, and isolations and pathogencity tests were conducted to determine the aetiology of a serious canker disease. Affected trees showed cankers on the scion that frequently began on the branches. Three Phytophthora species were identified based on their morphological, cultural, physiological and molecular profiles. Phytophthora citrophthora was the main species associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 20 publications
2
34
1
2
Order By: Relevance
“…However, to the authors' knowledge, this is the first report of trunk and branch canker caused by P. citrophthora in Tunisia on clementine. This new syndrome was reported first in Spain in 2008 (Alvarez et al, 2008) and then in South Africa in 2010 (Schutte et al, 2010). This disease could have a high economic impact as clementine production increases in Tunisia.…”
mentioning
confidence: 99%
“…However, to the authors' knowledge, this is the first report of trunk and branch canker caused by P. citrophthora in Tunisia on clementine. This new syndrome was reported first in Spain in 2008 (Alvarez et al, 2008) and then in South Africa in 2010 (Schutte et al, 2010). This disease could have a high economic impact as clementine production increases in Tunisia.…”
mentioning
confidence: 99%
“…Isolations from the bark of citrus tree revealed the presence of the fungus Phytophthora spp, the cause of citrus gummosis, affecting root crown and the branch. All thus features were also described by Farih, et al [19], Ali and canihos et al [20], Alvarez, et al [7]. isolated from citrus bark.…”
Section: Incubation and Isolationmentioning
confidence: 84%
“…Alvarez et al [7] reported that the citrus Cankers were more frequent on scions than rootstocks 92·4 and 7·6% of respectively. The disease mainly affected mature citrus trees; Diseased trees showed cankers and gum exudations mainly on aboveunion parts, especially on the major limbs, whereas rootstocks generally remained healthy.…”
Section: No Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gum exudation at the surface of the affected bark generally accompanies further development of the disease and extensive lateral invasion of the cambium through injuries or growth cracks results in girdling and weakening or death of the tree (Klotz & Calavan, 1969;Whiteside, 1971). Recently, P. citrophthora was identified to be the predominant species in orchard soils in Spain as well as the causal organism for branch cankers on Clementine mandarins (Alvarez et al, 2008). Fawcett (1936) described Phytophthora spp.…”
Section: Introductionmentioning
confidence: 99%